Effectiveness Of Using Virgin Coconut Oil Against Diaper Rash In Babies In PMB Syafriani, Nibong District North Aceh District - Komala Kartikasari Nst; Uswatul Muharramah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The World Health Organization (WHO) released data about babies who experience diaper rash. This results in as many as 250,000 out of 1,000,000 babies undergoing outpatient care who experience very severe diaper rash. This incident is most often found in babies aged around 1 year. The research aimed to analyze the effectiveness of virgin coconut oil (VCO) on diaper rash in babies at PMB Syafriani. The research method used a plan and strategy to carry out the research, which was included to answer the problems faced. The design of this research used a Quasi-experimental post-test only with a control group with a purposive sampling technique totaling 30 babies. The research results obtained were that the majority of respondents before being given the intervention had a mild/moderate diaper rash category of 14 respondents (46.7%) The majority of respondents after being given the intervention had a mild diaper rash category of 16 respondents (53.3%) Inuence The effectiveness of using Virgin Coconut oil against diaper rash in babies in PMB Syafriani, Nibong sub-district, North Aceh Regency with a sig value of 0.000 (p = value)